Amplitude variables of circle on the pedagogic pommel horse in Gymnastics - Baudry, L.; Sforza, C.; Leroy, D.; Lovecchio, N.; Gautier, G.; Thouvarecq, R. (The Journal of Strength and Conditioning Research, 2009)
The movement amplitude is a key component of numerous elements in gymnastics. The purpose of the present study is to highlight the most pertinent amplitude variable of the circle performed on the pedagogic pommel horse. Twelve gymnasts (6 expert gymnasts vs. 6 nonexpert gymnasts) performed 10 circles on this event. A Vicon 512 system was used to record the 3-dimensional position of 11 markers fixed on the gymnasts. Our results revealed than 4 amplitude variables permitted us to significantly discriminate the levels of performance of the gymnasts (p < 0.05): shoulder extension in front phase, body alignment, shoulder diameter, and ankle diameter. In a training perspective, this result could help coaches focus their advice and pedagogic situations on the pertinent technical criteria. Then, a stepwise discriminant analysis performed on the 4 previously selected variables showed that 2 variables allowed us to accurately discriminate the circle amplitude: ankle diameter and body alignment. These 2 variables can be used by coaches as a specific index to objectively determine the performance levels of gymnasts and to measure improvement in movements after specific training.